Actual cost of providing long-acting reversible contraception: a study of Implanon® cost. Issue 2 (1st April 2009) - Lipetz, Clare; Fleming, Charlotte; Phillips, Ceri
Abstract : Background: The National Institute for Health and Clinical Excellence (NICE) has judged Implanon® to be the most cost effective of the long-acting reversible contraception (LARC) methods, and its cost effectiveness is enhanced with increased duration of use. Gwent Sexual and Reproductive Health service provides unrestricted use of Implanon, and with the number of implants fitted increasing annually the service wanted to know how long clients were keeping their contraceptive implants in and the cost of implant provision. Methods: The actual cost of providing Implanon was calculated in a cohort of 493 patients within a community-based sexual and reproductive health service, and compared to that predicted in the NICE Clinical Guideline 30 on LARC. Results: The annual cost for the method (using Implanon) was £77.49, 25% lower than the estimate made by NICE, despite a shorter duration of use of the method. Conclusion: The actual cost in this community-based sexual and reproductive health service may not be transferable to other settings such as general practice.